Model Pendidikan Rahmatal Lil Alamin Dalam Pandangan Al-Qur’an dan Hadis - Prayogi Ibrahim; Kasim Yahiji; Rahmin Thalib Husain; Ilyas Daud (IHSANIKA : Jurnal Pendidikan Agama Islam, 2024)
This research discusses the Islamic education model Rahmatal Lil Alamin in view of the Al-Qur'an and Hadith. This research is qualitative research in the nature of library research, with the main objects being books and other documents. Data collection for this research was carried out by collecting books on educational models and the concept of rahmatal lil alamin. The concept of rahmatan lil alamin is a prophetic mission, namely to make people pious individually, namely to invite people to be devout to Allah SWT. Apart from that, it makes social righteousness by proving that Islam is rahmatan lil alamin. One form of social piety is maintaining harmonious harmony between religious communities which is a pillar of social life. For this reason, the presence of Islam rahmatan lil alamin conceptually as a form of social transformation functions to shape the social character of Islam which is tolerant and humanist.